2015
DOI: 10.3201/eid2104.140245
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis E Virus Antibodies, Israel, 2009–2010

Abstract: We investigated prevalence of hepatitis E virus in a sample of the population of Israel. The overall seroprevalence of antibodies to the virus was 10.6% (95% CI 8.4%–13.0%); age-adjusted prevalence was 7.6%. Seropositivity was associated with age, Arab ethnicity, low socioeconomic status, and birth in Africa, Asia, or the former Soviet Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Human serum samples were collected from: Bedouins living in the southern district, in tribes that own dromedary camels (overall 305; 296 tested for the first time in this study and nine added from our previous study [21]), non-Bedouin Arabs (overall 320; 297 from the present study and 23 from our previous study [21]) and from Jews (195 samples presented in our previous study [21]). All human samples were randomly selected using an age-stratified sampling design from the stored sera bank of the Israeli Centre for Disease Control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human serum samples were collected from: Bedouins living in the southern district, in tribes that own dromedary camels (overall 305; 296 tested for the first time in this study and nine added from our previous study [21]), non-Bedouin Arabs (overall 320; 297 from the present study and 23 from our previous study [21]) and from Jews (195 samples presented in our previous study [21]). All human samples were randomly selected using an age-stratified sampling design from the stored sera bank of the Israeli Centre for Disease Control.…”
Section: Methodsmentioning
confidence: 99%
“…Human HEV infection, investigated using seroprevalence studies, was found to be more prevalent in older ages [7][8][9][10][11][12][13][14][15][16][17][18][19][20], lower socio-economic status [21], poorer residence areas [9,[14][15], among sheltered homeless adults [22] or uneducated people [14], specific nationalities (for example, higher in mixed race donors and ethnic groups within China [12,15], or in immigrants from Afghanistan [14]), drinking water from wells or rivers [15], consumption of meat products [7,15,17,23] especially pork [24,25] and following blood transfusions [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Unlike the ongoing surveillance for polio, there is no HEV monitoring in Israel. The overall prevalence of anti-HEV IgG antibodies in Israel was recently found to be 10.6%, 4 but in a study that retrospectively assessed acute HEV infections in Israel between 1993 and 2013, only 68 HEV positive cases were identified (∼3 per year). 5 HEV has already been identified in sewage and in other environmental samples in several Mediterranean and Middle East countries, [6][7][8] but not in Israel.…”
Section: Introductionmentioning
confidence: 99%
“…As no clinical signs of viral hepatitis were recalled, we assume that HEV infection in these individuals was silent. Previously, we have reported a much lower overall seroprevalence (10.6%) for anti-HEV antibodies in the general Israeli population [28]. Higher prevalence of antibodies to HEV virus in swine workers compared with normal blood donors has already been reported in the United States and other countries [29,30] and demonstrates the high risk for HEV infection among individuals regularly exposed to infected animals.…”
Section: Discussionmentioning
confidence: 84%